HUBUNGAN KARAKTERISTIK, PENGETAHUAN, DAN SIKAP DENGAN KEBIASAAN MEROKOK KELUARGA MISKIN DI WILAYAH KERJA PUSKESMAS GUNUNG TUA KECAMATAN PANYABUNGAN KABUPATEN MANDAILING NATAL TAHUN 2012 - Mawaddah warrahma (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACT Smoking is one habit or lifestyle is not good. smoking behavior seen from different points of view is very harmful, both for himself and those around him. In addition to adversely affect the healthy, smoking habbit will impact economic losses large enough for the family and the community. Indonesian Forum on Parliamentarians for Population and Development (IFPPD) reveals the link cigarettes with poverty. Two of the three fathers in Indonesia are smokers. With poor families in Indonesia reached 19 million, 12 million heads of poor households to be smokers. The type of the research was analytic with design cross secsional. Data analysis using chi square test with a total sample are 95 poor households. This research purpose to determine the relationship characteristics, knowledge, and attitudes with smoking habits of poor families in the working area Gunung Tua Puskesmas Kecamatan Panyabungan Kabupaten Mandailing Natal. The results of the research showed that there was no relationship between respondents age with smoking habit (p = 0, 943), there was no relationship between education with smoking habit (p = 1,000), there was the relationship between respondents work with smoking habit (p = 0, 003), there was the relationship between respondents income with smoking habit (p < 0, 001), there was no relationship between respondents knowledge about cigarette with smoking habit (p = 0, 665), there was the relationship between respondents attitude with smoking habit (p = 0, 002), and there was the relationship between respondents psychological with smoking habits (p = 0, 032). It is recommended that health workers at Gunung Tua Puskesmas and the agencies related to it should provide counseling, make a program about the dangers of smoking, approach to poor families and work with families in an effort to minimize or even eliminate the smoking habit.